Penilaian Ekonomi Ekosistem Hutan Mangrove di Kawasan Cagar Alam Hutan Bakau Pantai Timur Desa Alang-Alang Kecamatan Muara Sabak Timur Kabupaten Tanjung Timur - Fazriyas, Fazriyas; Destiani, Retno; Albayudi, Albayudi (Fakultas Kehutanan Universitas Jambi, 2018)
The purpose of this study was to determine the benefit and value of mangrove forest ecosystems on Cagar Alam Hutan Bakau Pantai Timur in the Alang-alang village region, the concept of economic valuation used to quantify the total value of direct benefits and value of the indirect benefits that exist. This research was conducted by field observations and interviews on the field against the respondents using a questionnaire guide. Based on the results obtained mangrove forest ecosystem in the Alang-alang village region has a total economic benefit value of Rp 291.037.310/year with a value contributor greatest benefit is direct benefits value in the form of Non-Timber Forest Products (honey, catching fish, crabs, shrimp, and scallops). The calculation of direct benefits value that is by using the market price method, the results of direct benefit Rp 259.479.000/year. As for the indirect benefits valuation that an assessment of the ecological functions of the area as a seawater intrusion barrier to the success of the productivity of coconut plantation owned by the community with the method of productivity changes to the indirect benefits value obtained Rp 31.567.310/year. Total economic value can be used as a reference or a basis of comparison for the community and the government in determining the policy of the management and utilization of existing mangrove forests.